Dietary intake methods in the anthropology of food and nutrition - Ulijaszek, S (Berghahn Books, 2004)
Dietary and nutritional studies in anthropology may attempt to address issues in which food and nutrition are central, or where diet may be a peripheral or contributory component of a complex of problems within a group, population or society. Studies may be concerned with nutritional factors or they may be concerned with food symbolism, the perception of food, or the role of food in forging and maintaining identity. Dietary intake studies can be used to inform the study of food consumption, nutrient intake and nutritional status. Thus the range of ways that dietary intake studies can serve anthropological enquiry is extremely broad. The choice of method or methods should involve the degree of appropriateness for the question in hand, the accuracy, precision, complexity, and cost (in time and money) of the techniques chosen, and the ease of subsequent interpretation of quantitative results. This is often not straightforward, and the aim of this chapter is to examine critically some of the problems associated with the choice and use of dietary methods in determining food and nutrient intake, and in estimating nutritional status from nutrient intake. Various books have been written about measurement of diet and nutritional intake, and nutritional status assessment from dietary intakes. Most of them consider the role of dietary and nutritional factors in human health. Volumes considering the study of diet and nutrition in anthropology include those edited by Johnston (1987) and Pelto et al. (1989) and written by Ulijaszek and Strickland (1993). Readers wanting more information than is possible to give in the present chapter are guided to these volumes.